Resonant absorption effects induced by polarized laser light irradiating thin foils in the TNSA regime of ion acceleration. (12th April 2016) - Torrisi, L.; Badziak, J.; Rosinski, M.; Zaras-Szydlowska, A.; Pfeifer, M.; Torrisi, A.
Abstract: Thin foils were irradiated by short pulsed lasers at intensities of 10 16−19 W/cm 2 in order to produce non-equilibrium plasmas and ion acceleration from the target-normal-sheath-acceleration (TNSA) regime. Ion acceleration in forward direction was measured by SiC detectors and ion collectors used in the time-of-flight configuration. Laser irradiations were employed using p-polarized light at different incidence angles with respect to the target surface and at different focal distances from the target surface. Measurements demonstrate that resonant absorption effects, due to the plasma wave excitations, enhance the plasma temperature and the ion acceleration with respect to those performed without to use of p-polarized light. Dependences of the ion flux characteristics on the laser energy, wavelength, focal distance and incidence angle will be reported and discussed.